Reconstructing Islamic Education Values in the Three Day Khuruj Activities of Jamaah Tabligh as a Model for Strengthening Vocational Students’ Character - Raden Sumiadi; Gita Sarwadi; Syahrir (Lembaga Bale Literasi, 2025)
This study is motivated by the growing need for character-strengthening models for vocational students that emphasize not only technical competencies but also the development of religious character, integrity, responsibility, discipline, and social concern. Although various approaches to character education have been developed, research positioning experiential religious activities as a source of character learning remains limited. One activity with significant potential in this regard is the three-day khuruj conducted by Jamaah Tabligh, which incorporates educational practices emphasizing religious habituation, da'wah, discipline, cooperation, independence, simplicity, and the strengthening of social relationships. This study aims to reconstruct the Islamic educational values embedded in the three-day khuruj activity into a model for strengthening vocational students' character, using a qualitative case study approach conducted within a Jamaah Tabligh community that routinely engages in three-day khuruj activities. Participants included amir, khuruj participants, former khuruj participants, community leaders, and academics. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed interactively through data reduction, data display, and conclusion drawing and verification, with credibility ensured through source, methodological, and time triangulation. The findings indicate that the three-day khuruj embodies Islamic educational values internalized through habituation, role modeling, direct experience, spiritual reflection, and social interaction—including sincerity, discipline, responsibility, independence, ukhuwah Islamiyah, social concern, simplicity, trustworthiness, leadership, communication, cooperation, self-control, istiqamah, and time management. These values were subsequently reconstructed into a character-strengthening model emphasizing direct experience as the core mechanism for sustainable character formation, offering a contextual and applicable approach to developing vocational human resources who are professional, possess integrity, and demonstrate noble character.